Polypharmacy and trajectories of health-related quality of life in older adults: an Australian cohort study - Aljeaidi, Muhamad S; Haaksma, Miriam L; Tan, Edwin C K (My University, 2022)
Health-related quality of life (HRQoL) is an important outcome measure when considering medical treatment; however, the impact of polypharmacy on trajectories of HRQoL over time is unknown. This study aimed to investigate the association between polypharmacy status and trajectories of HRQoL in older adults. A longitudinal cohort study of 2181 community-dwelling adults, 65 years and older, who participated in the 2013 to 2017 waves of the Household Income and Labour Dynamics in Australia (HILDA) Survey. Polypharmacy was defined as the regular use of ≥ 5 prescription medications. Polypharmacy status was categorised into no polypharmacy, in 2013 only (baseline only polypharmacy), in 2017 only (incident polypharmacy) or at both time points (persistent polypharmacy). HRQoL was assessed through the SF-36 questionnaire generating two summary scores: physical component summary (PCS) and mental component summary (MCS). Linear mixed-effects models stratified according to polypharmacy status and change in comorbidities were used to assess trajectories of HRQoL. Older adults with persistent polypharmacy had lowest scores for HRQoL measures from 2013 to 2017. After adjusting for all covariates, those with incident polypharmacy had the steepest annual decline in both the PCS and MCS: - 0.86 in PCS and - 0.76 in MCS for those with decreasing or stable comorbidities, and - 1.20 in PCS and - 0.75 in MCS for those with increasing comorbidities. Polypharmacy was associated with poorer HRQoL, even after adjusting for confounders. Incident polypharmacy was found to be associated with a clinically important decline in HRQoL and this should be considered when prescribing additional medication to older adults.
Quality of Life Research
Keywords: Ageing; Health and wellbeing